Pengaruh Penggunaan Media Pembelajaran Komik Terhadap Hasil Belajar Matematika Siswa Materi Teorema Pythagoras - Fatin Iftinani; Syahrul Azmi; Tabita Wahyu Triutami (Griya Journal of Mathematics Education and Application, 2026)
This study was motivated by the low mathematics learning outcomes of students on the Pythagorean Theorem material, as indicated by difficulties in understanding concepts and low student participation during the learning process. The instructional media used by teachers have not been able to optimally attract students’ attention; therefore, alternative learning media that are more engaging and easier to understand are needed. This study aims to determine the effect of comic-based learning media on the mathematics learning outcomes of eighth-grade students at SMP Negeri 1 Lembar in the 2025/2026 academic year. This study employed a quantitative approach using a Posttest-Only Control Group Design. The research sample consisted of two classes selected using the cluster random sampling technique, namely class VIII B as the experimental class consisting of 33 students and class VIII D as the control class consisting of 32 students. The experimental class was taught using comic-based learning media, while the control class received instruction without the use of comic media. Data were collected through a posttest administered after two learning sessions and analyzed using descriptive statistics, an Independent Samples t-test, and effect size calculations. The results showed that , which is greater than , indicating a significant difference in learning outcomes between the two classes. The mean learning outcome of the experimental class was higher than that of the control class, with an effect size of 1.381, which falls into the large category. Thus, comic-based learning media have a positive and significant effect on students’ mathematics learning outcomes.